Ameliorative effect and mechanism of Yi‐Suan‐Cha against hyperuricemia in rats. Issue 8 (12th July 2021) - Qin, Yuanyuan; Zhang, Xuan; Tao, Hui; Wu, Yangyang; Yan, Jie; Liao, Lin; Meng, Jianjun; Lin, Faquan
Abstract: Background: This study aimed to evaluate the urate‐lowering effects of Yi‐Suan‐Cha and explore its underlying mechanisms in experimental hyperuricemia induced in rats. Methods: Forty‐eight male SD rats were randomly allocated into normal control, model, allopurinol, benzbromarone, low‐dose Yi‐Suan‐Cha (0.2 g/ml), and high‐dose Yi‐Suan‐Cha (0.4 g/ml) groups ( n  = 8 rats per group). Rat models of hyperuricemia were established through intragastric administration of adenine 25 mg/kg + potassium oxalate 300 mg/kg for 3 weeks. After the last administration, serum uric acid, creatinine, and urea nitrogen levels were measured. Renal histopathology was observed by hematoxylin‐eosin staining. Xanthine oxidase level in serum and liver homogenates was measured by ELISA. The protein and mRNA expression of URAT1, ABCG2, OAT1, and GLUT9 in the kidney was detected by Western blotting and RT‐PCR, respectively. Results: The serum uric acid levels were significantly lowered in all medication groups than in the model group. The benzbromarone and both Yi‐Suan‐Cha groups showed clear kidney structures with no obvious abnormalities. Compared with the normal control group, the model group showed increased URAT1/GLUT9 protein expression and decreased ABCG2/OAT1 protein expression. Compared with the model group, both Yi‐Suan‐Cha groups showed decreased URAT1/GLUT9 protein expression and increased ABCG2/OAT1 protein expression. Compared with that in the normal control group, URAT1/GLUT9 mRNA expression increased in the model group. Compared with the model group, the low‐dose and high‐dose Yi‐Suan‐Cha groups showed decreased URAT1/GLUT9 mRNA expression and increased ABCG2/OAT1 mRNA expression. Conclusion: Yi‐Suan‐Cha may lower uric acid level by downregulating URAT1/GLUT9 expression and upregulating ABCG2/OAT1 expression. Abstract : Effects of Yi‐Suan‐Cha on the protein levels of renal transporters. Proteins were extracted from the kidney for Western blot analysis of URAT1 (A, B), ABCG2 (A, C), OAT1 (A, D), and GLUT9 (A, E).